Do maternal haemodynamics have a causal influence on treatment for gestational diabetes? - Abigail R. Anness; Michael Foster; Mohammed W. Osman; David Webb; Thompson Robinson; Asma Khalil; Neil Walkinshaw; Hatem A. Mousa (Journal of Obstetrics and Gynaecology)
Background Arterial stiffening is believed to contribute to the worsening of insulin resistance, and factors which are associated with needing pharmacological treatment of gestational diabetes (GDM), such as maternal obesity or advanced age, are associated with impaired cardiovascular adaptation to pregnancy. In this observational study, we aimed to investigate causal relationships between maternal haemodynamics and treatment requirement amongst women with GDM.Methods We assessed maternal haemodynamics in women with GDM, comparing those who remained on dietary treatment with those who required pharmacological management. Maternal haemodynamics were assessed using the Arteriograph® (TensioMed Ltd, Budapest, Hungary) and the NICOM® non-invasive bio-reactance method (Cheetah Medical, Portland, Oregon, USA). A graphical causal inference technique was used for statistical analysis.Results 120 women with GDM were included in the analysis. Maternal booking BMI was identified as having a causative influence on treatment requirement, with each unit increase in BMI increasing the odds of needing metformin and/or insulin therapy by 12% [OR 1.12 (1.02 − 1.22)]. The raw values of maternal heart rate (87.6 ± 11.7 vs. 92.9 ± 11.90 bpm, p = 0.014) and PWV (7.8 ± 1.04 vs. 8.4 ± 1.61 m/s, p = 0.029) were both significantly higher amongst the women requiring pharmacological management, though these relationships did not remain significant in causal logistic regression.Conclusions Maternal BMI at booking has a causal, rather than simply associational, relationship on the need for pharmacological treatment of GDM. No significant causal relationships were found between maternal haemodynamics and the need for pharmacological treatment.